Multicultural Learning: Christian Students at Muhammadiyah Mayong Senior High School - Toni Ardi Rafsanjani; M. Abdurrozaq; Roynaldy Saputro (Walidem Institute and Publishing (WIP), 2025)
Objective: Multicultural learning is a vital approach in education aimed at enhancing intercultural understanding and tolerance. This study explores the experiences of Christian students at SMA Muhammadiyah Mayong, an Islamic-based school, within the context of multicultural learning, the study examines how Christian students interact with their Muslim peers and how multicultural values are integrated into the teaching and learning processes. Theoretical framework: The theoretical framework is grounded in the concept of multicultural education, emphasizing the importance of recognizing diversity and fostering mutual respect in educational environments. Literature Review: A review of the literature supports this approach, highlighting the role of education in building social cohesion in pluralistic societies. Methods: The research methods included in-depth interviews, observations, and document analysis. Data were collected from Christian students, teachers, and parents to provide a holistic understanding of the dynamics of multicultural learning in the school. Results: The findings reveal that Christian students at SMA Muhammadiyah Mayong experience an inclusive learning environment where religious and cultural differences are appreciated. Positive interfaith interactions contribute to fostering tolerance and mutual respect among students. Additionally, the teaching process prioritizes universal values, such as justice and humanity, as fundamental principles. However, challenges such as stereotypes and prejudices occasionally arise. Nevertheless, open dialogue between students, teachers, and parents has successfully created a supportive atmosphere for multicultural learning. Implications: The implications of this study underscore the importance of developing a more inclusive and culturally responsive curriculum in Indonesia. Beyond academic benefits, multicultural learning enriches students’ social experiences by fostering solidarity and social awareness. Novelty: The novelty of this research lies in its unique focus on the experiences of minority students in an Islamic-based school, a topic rarely explored in previous studies. It provides new insights into how multicultural education can be implemented in the context of religious diversity and its potential to promote social cohesion. Through multicultural education, young generations are expected to become agents of peace and unity in a pluralistic society. The findings of this study can serve as a reference for the development of inclusive educational policies in Indonesia.